Learning Chef - Taylor, Mischa (O'Reilly Media, 2015)
Get a hands-on introduction to the Chef, the configuration management tool for solving operations issues in enterprises large and small. Ideal for developers and sysadmins new to configuration management, this guide shows you to automate the packaging and delivery of applications in your infrastructure. You'll be able to build (or rebuild) your infrastructure's application stack in minutes or hours, rather than days or weeks. After teaching you how to write Ruby-based Chef code, this book walks you through different Chef tools and configuration management concepts in each chapter, using detailed examples throughout. All you need to get started is command-line experience and familiarity with basic system administration. Configure your Chef development environment and start writing recipes Create Chef cookbooks with recipes for each part of your infrastructure Use Test Kitchen to manage sandbox testing environments Manage single nodes with Chef client, and multiple nodes with Chef Server Use data bags for storing shared global data between nodes Simulate production Chef Server environments with Chef Zero Classify different types of services in your infrastructure with roles Model life stages of your application, including development, testing, staging, and production.